To the selection of the composition of dry-formed concrete - M.S. Egamberdiev (Global Scientific Publishing, 2022)
The essence of the method lies in the fact that the dry concrete mixture is compacted, its volume is fixed and then impregnated with water. As studies in the field of physicochemical mechanics have shown, during vibratory action, bulk materials acquire the fluidity characteristic of a liquid binder. Under certain parameters, the condition of the material, as well as the impact of vibration, it is possible to limit the compaction of bulk materials. In contrast to the wet method of concreting, dry concreting does not have the traditional dependence "workability - water content". In this regard, the approach to the selection of the composition of concrete changes significantly. On the basis of studies conducted by Khutortsov GM, Osin B.V. and Ovchinnikov IP, Some abilities of dry concreting are determined. It has been established that all kinds of materials are used for the preparation of a dry concrete mixture (materials with a moisture content of up to 0 5%); Squeaks, mostly finegrained, and crushed stone with a size of up to 10 mm are used as aggregates, with SBS compaction It is necessary to use with a load of 100-150 g/cm2; Impregnation with water is carried out only after fixing the volume of compacted SBS.
Keywords: durability; concrete condition; structure; drainage